People participating in the 1986 y-Walk - Unknown:::Creator::::::::::::
Negative shows a group of men and women participating in the 1986 y-Walk. They are walking down Almaden Boulevard. Some of them are wearing tee shirts that read: "Walk for women. YWCA 1986." The woman walking in the front, far left, appears to be African American and is probably Jenifer Williams. The street is landscaped with ivy and trees.